Irritable bowel syndrome: A concise review of current treatment concepts - Wall, Geoffrey C (Baishideng Publishing Group Inc, 2014)
Irritable bowel syndrome (IBS) is one of the most common gastrointestinal disorders causing patients to seek medical treatment. It is relatively resource intensive and the source of significant morbidity. Recent insights into the pathophysiology and treatment of IBS has given clinicians more options than ever to contend with this disorder. The purpose of our paper is to review older, “classic” treatments for IBS as well as newer agents and “alternative” therapies. We discuss the evidence base of these drugs and provide context to help develop appropriate treatment plans for IBS patients.